99 How are outcomes of specialist palliative care measured in different patient populations and settings?. (14th March 2023) - Stenson, Charlotte; Dewhurst, Felicity; Frew, Katie; Hanratty, Barbara
Abstract : Background: Outcome measurement is key to delivering effective, high quality, patient-centred care, as well as commissioning of services. The diversity of patient populations and service models in palliative care makes demonstrating efficacy and comparing services challenging. Aims: 1. To synthesise the evidence on how outcomes of specialist palliative care are currently measured in different populations and care settings. 2. To identify the evidence gaps where specialist palliative care services are under-evaluated. Design: A scoping systematic review of reviews. Data sources: Five databases (MEDLINE, EMBASE, CINAHL, Cochrane Library and Epistemonikos) were searched for reviews published between 2010–2021. Included reviews reported on outcomes of specialist palliative care in an adult population with life-limiting illness. Findings from the reviews were grouped, narratively summarised and compared. Results: 79 reviews met inclusion criteria. There was significant heterogeneity in the specialist palliative care services evaluated and the outcome measures and study designs used in the primary reviews. Health-related quality of life and symptom burden were the most frequently measured patient outcomes across care settings and populations. Health-system outcomes focussed predominantly on place of death and health service utilisation. There is a lack of evidence on outcomes of outpatient services, hospice care and telehealth services. The majority of evidence on population-specific outcomes is focussed on solid-organ malignancy. Evidence in populations with frailty, dementia, multiple long-term conditions and minority ethnic groups is lacking. Conclusion: Palliative care research is limited by a lack of cohesion in use of outcome measures and under-evaluated areas of practice. Expansion and adaptation of services should be driven by a co-ordinated approach to outcome measurement, as well as increased efforts to capture experiences across the breadth of community settings and in non-malignant disease.